Light-Induced Therapies for Prostate Cancer Treatment - Ferroni, Claudia; Del Rio, Alberto; Martini, Cecilia; Manoni, Elisabetta; Varchi, Greta (Frontiers in Chemistry, 2019)
Prostate cancer (PC) is one of the most widespread tumors affecting the urinary system and the fifth-leading cause from cancer death in men worldwide. Despite PC mortality rates have been decreasing during the last years, most likely due to an intensification of early diagnosis, still more than 300,000 men die each year because of this disease. In this view, researchers in all countries are engaged in finding new ways to tackle PC, including the design and synthesis of novel molecular and macromolecular entities able to challenge different PC biological targets, while limiting the extent of unwanted side effects that significantly limit men’s life quality. Among this field of research, photo-induced therapies, such as photodynamic and photothermal therapies (PDT and PTT), might represent an important advancement in PC treatment due to their extremely localized and controlled cytotoxic effect, as well as their low incidence of side effects and tumor resistance occurrence. Based on these considerations, this review aims to gather and discuss the last five-years literature reports dealing with the synthesis and biological activity of molecular conjugates and nano-platforms for photo-induced therapies as co-adjuvant or combined therapeutic modalities for the treatment of localized PC.